The Impact of Deep Core Muscle System Training Through Virtual Reality on Selected Posturographic Parameters - Jakub Čuj; Denisa Lenková; Miloslav Gajdoš; Eva Lukáčová; Michal Macej; Katarína Hnátová; Pavol Nechvátal; Lucia Demjanovič Kendrová (Journal of Functional Morphology and Kinesiology, 2025)
Objective: The aim of this study was to investigate the immediate effects of deep core muscle training in the plank position, using the Icaros® system, integrated with virtual reality (VR), on selected posturographic parameters. Methods: To meet the stated objective, we utilized the Icaros® therapeutic system (Icaros GmbH, Martinsried, Germany) for VR-based exercise. The posturographic parameters were measured using the FootScan® force platform (Materialise Motion, Paal, Belgium). A representative sample of 30 healthy participants, 13 females and 17 males (age: 22.5 ± 2.1 years; weight: 65 ± 2.9 kg; height: 1.68 ± 0.4 m; BMI: 23.04 ± 1.75) was included in the study. All participants had no prior experience with VR. The selected posturographic parameters were the ellipse area (mm2) and traveled distance (mm), assessed four times at five-minute intervals, following a 15 min VR-based training session on the Icaros® system. Results: The results revealed that the participants experienced a sense of instability after completing the 15 min VR session, as objectively demonstrated by changes in the measured parameters. Both the ellipse area and traveled distance showed a worsening trend during the first three measurements: immediately post-exercise, at 5 min, and at 10 min post-exercise. A downward trend was observed in the fourth measurement, taken 15 min after exercise. Statistically significant differences were found between both parameters: ellipse area (p = 0.000) and traveled distance (p = 0.000). Post hoc analysis further confirmed significant differences between the time points. Conclusions: Based on the findings, it is recommended that trainers and physiotherapists supervising athletes or patients using the Icaros® VR system allow for a minimum rest period of 15 min in a seated or lying position following exercise. This recovery period appears essential to mitigate the sensation of instability and to reduce the risk of complications or injury due to potential falls.